COUMARIN (ESCULETIN) - AN ANTIRHEUMATOID ARTHRITIC COMPOUND: AN UPDATE - S, Jaya Kumari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Context: Esculetin is a natural polyphenolic compound. It is chemically 6,7-dihydroxycoumarin and one of the ingredients of Cortex fraxini, a Chinese traditional medicine. It is used as a dietary supplement and found as non-toxic. Recently, there are many research works evaluated on esculetin in arthritis with supported molecular mechanisms. Objectives: Esculetin becoming more attractive prodrug for arthritis. Hence, the present minireview will consolidate the targeted site of esculetin in the treatment of arthritis over the past decade. Results: The most important molecular mechanism of esculetin is an antioxidant activities with decreased level of reactive oxygen species/reactive nitrogen species. It also inhibited lipoxygenase 5, lipoxygenase 12, and tyrosinase enzymes. It reduces the inflammation by modulating the key inflammatory enzyme matrix metalloproteinase-1 activity. It also lowers the nitrous oxide and prostaglandin E2 level in synovial fluid. Esculetin derivatives such as 5-methoxy esculetin inhibited the activity of nitrogen-activated protein kinases. The updated data also reveal that esculetin suppresses the leukotriene B4 level in plasma of adjuvant-induced arthritis tested animals. Conclusion: The presented update showed that esculetin may be useful as a tool in regulating the mechanism and physiological functions of the inflammatory mediators and enzyme. Hence, the presented review work may be considered as a scientific proof for the development of an attractive drug candidate for the patient with rheumatoid arthritis.